1997
DOI: 10.1046/j.1471-4159.1997.69041484.x
|View full text |Cite
|
Sign up to set email alerts
|

A Temporary Local Energy Pool Coupled to Neuronal Activity: Fluctuations of Extracellular Lactate Levels in Rat Brain Monitored with Rapid‐Response Enzyme‐Based Sensor

Abstract: A successfully developed enzyme-based lactate microsensor with rapid response time allows the direct and continuous in vivo measurement of lactic acid concentration with high temporal resolution in brain extracellular fluid. The fluctuations coupled to neuronal activity in extracellular lactate concentration were explored in the dentate gyrus of the hippocampus of the rat brain after electrical stimulation of the perforant pathway. Extracellular glucose and oxygen levels were also detected simultaneously by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
352
3
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(387 citation statements)
references
References 36 publications
30
352
3
2
Order By: Relevance
“…This study and several others (e.g., De Bruin et al, 1990;Kuhr et al, 1988;Van der Kuil and Korf, 1991;Krugers et al, 1992) show that lactate is formed under conditions of enhanced neural activity which is-at least in part-associated with lower extracellular glucose. The time course of hippocampus lactate after a single stimulation (lasting 5 secs; Hu and Wilson, 1997) and detected with the biosensors is very similar to that seen with continuous flow analysis of microdialysates in rats, subjected to a single electroconvulsive stimulus with an intact entorhinalhippocampal glutamatergic pathway (Krugers et al, 1992). Modelling shows that such a time course can best be described by a very rapid (nearly immediate) increase of intracellular lactate that is subsequently released into the extracellular compartment via a carrier-mediated process (Kuhr et al, 1988).…”
supporting
confidence: 57%
“…This study and several others (e.g., De Bruin et al, 1990;Kuhr et al, 1988;Van der Kuil and Korf, 1991;Krugers et al, 1992) show that lactate is formed under conditions of enhanced neural activity which is-at least in part-associated with lower extracellular glucose. The time course of hippocampus lactate after a single stimulation (lasting 5 secs; Hu and Wilson, 1997) and detected with the biosensors is very similar to that seen with continuous flow analysis of microdialysates in rats, subjected to a single electroconvulsive stimulus with an intact entorhinalhippocampal glutamatergic pathway (Krugers et al, 1992). Modelling shows that such a time course can best be described by a very rapid (nearly immediate) increase of intracellular lactate that is subsequently released into the extracellular compartment via a carrier-mediated process (Kuhr et al, 1988).…”
supporting
confidence: 57%
“…It should be noted that there is some evidence that a slight, transient decrease in local pO 2 may occur during the first few hundred milliseconds of neural activation. 39 However, if this occurs, it would be quickly supplanted by a longer lasting hyperemia and increase in oxygen availability. 44,45 Thus, even if a transient hypoxia occurs at the beginning of visual stimulation, it cannot be the cause of the sustained elevation of lactate observed in the PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is now known that lactate accumulation occurs regularly under aerobic conditions in the brain and other tissues and that lactate is an important metabolic fuel. 35,36 Although its exact role as a metabolic fuel is not yet fully understood, studies have shown that lactate is the end product of glycogenolysis in astroglia, 37,38 that accumulation of lactate in brain parenchyma is a normal occurrence during neural activation under fully aerobic conditions 39,40 and that lactate is a significant substrate for neuronal oxidative metabolism. 36,41 The hypoxia model of PD interprets the exaggerated brain lactate responses to alkalosis as confirmation that alkalosisinduced vasoconstriction has caused hypoxia in the PD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that lactate might serve a similar role in brain energy metabolism (Pellerin et al, 1998;Schurr, 2005). In vivo measures of brain lactate with microsensors in rats (Hu and Wilson, 1997) and with proton magnetic resonance spectroscopy (1H-MRS) in humans (Prichard et al, 1991;Sappey-Marinier et al, 1992;Frahm et al, 1996) have demonstrated brain lactate increases during neuronal activation. These 1H-MRS studies suggests that noninvasive measures of activity-stimulated lactate responses can be used to study brain function in humans.…”
Section: Introductionmentioning
confidence: 99%